Transient kinetic studies reveal isomerization steps along the kinetic pathway of Thermus thermophilus 3‐isopropylmalate dehydrogenase. (11th March 2013) - Gráczer, Éva; Lionne, Corinne; Závodszky, Péter; Chaloin, Laurent; Vas, Mária
<x xml:space="preserve">Abstract</x> To identify the rate‐limiting step(s) of the 3‐isopropylmalate dehydrogenase‐catalysed reaction, time courses of NADH production were followed by stopped flow (SF) and quenched flow (QF). The steady state kcat and Km values did not vary between enzyme concentrations of 0.1 and 20 μm. A burst phase of NADH formation was shown by QF, indicating that the rate‐limiting step occurs after the redox step. The kinetics of protein conformational change(s) induced by the complex of 3‐isopropylmalate with Mg2+ were followed by using the fluorescence resonance energy transfer signal between protein tryptophan(s) and the bound NADH. A reaction scheme was proposed by incorporating the rate constant of a fast protein conformational change (possibly domain closure) derived from the separately recorded time‐dependent formation of the fluorescence resonance energy transfer signal. The rate‐limiting step seems to be another slower conformational change (domain opening) that allows product release.